2009
DOI: 10.1128/iai.01022-08
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Stimulating Factor-1-Dependent Macrophage Functions Regulate the Maternal Decidua Immune Responses againstListeria monocytogenesInfections during Early Gestation in Mice

Abstract: The association between extreme-prematurity births and intrauterine infection emphasizes the importance of understanding the host immune responses against uterine-invading microbes during early pregnancy to the prevention of preterm births. Listeria monocytogenes, a clinically relevant intracellular bacterium, has a predilection for replication at the maternofetal interface during pregnancy. Here, using mice carrying the recessive null osteopetrotic mutation in the colony-stimulating factor-1 (CSF-1) gene, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 61 publications
2
23
0
1
Order By: Relevance
“…Singh et al (58) indeed reported that decidual Mf were highly capable of recognizing and phagocytosing bacteria. Further supporting this notion, M-CSF-deficient mice were more susceptible to pregnancy loss caused by Listeria monocytogenes infection (59), and IL-10-deficient mice were more susceptible to fetal loss induced by LPS (60,61) and the TLR9 ligand CpG (62), as compared with wild-type mice. Thus, these results indicate a crucial role for decidual Mf, not only in supporting an antiinflammatory environment, but also in the protection of the fetus against invading pathogens and infections, which, if uncontrolled, might cause spontaneous abortions or preterm labor.…”
Section: Discussionsupporting
confidence: 60%
“…Singh et al (58) indeed reported that decidual Mf were highly capable of recognizing and phagocytosing bacteria. Further supporting this notion, M-CSF-deficient mice were more susceptible to pregnancy loss caused by Listeria monocytogenes infection (59), and IL-10-deficient mice were more susceptible to fetal loss induced by LPS (60,61) and the TLR9 ligand CpG (62), as compared with wild-type mice. Thus, these results indicate a crucial role for decidual Mf, not only in supporting an antiinflammatory environment, but also in the protection of the fetus against invading pathogens and infections, which, if uncontrolled, might cause spontaneous abortions or preterm labor.…”
Section: Discussionsupporting
confidence: 60%
“…The relevance of these cytokines in pregnancy is further supported by their increased levels at the fetal-maternal interface (37,43), as well as by observations of increased rates of spontaneous abortions in M-CSF-deficient mice (44) and in mice with a local defect in IL-10 production (45). In addition, both M-CSF-deficient mice (46) and IL-10-deficient mice (47,48) show increased susceptibility to infection-induced fetal loss. Thus, it is likely that placental-derived M-CSF and IL-10 promote macro- + T cells exposed to 6.25% PE CM was partially reversed by the addition of neutralizing Abs against TGF-b (C), IL-10R (D), or TRAIL (E).…”
Section: Foxp3mentioning
confidence: 99%
“…The early stage of the host response in the decidua is particularly important because preexisting maternal adaptive T cell immunity does not protect the maternal-fetal interface from infection with L. monocytogenes (23). Interestingly, pregnant CSF-1 mutant op/op mice, which lack macrophages, and artificially decidualized macrophage-depleted mice show increased L. monocytogenes burdens within the placenta and uterus at 2 to 3 days postinfection, raising the possibility that macrophages control L. monocytogenes within the pregnant uterus (24). However, given that L. monocytogenes traffics from the maternal spleen and liver to the uterus (25), these results may be secondary to increases in the splenic or hepatic listerial burden.…”
mentioning
confidence: 99%